COMPARATIVE STUDY OF THE CRIMINAL ACT OF DEFAMATION ON SOCIAL MEDIA IN LAW NUMBER 1 OF 2024 CONCERNING ELECTRONIC INFORMATION AND TRANSACTIONS - Rahmat Setiawan Sembiring; Satino (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to conduct a comparative study of criminal acts of defamation on social media based on the provisions stipulated in Law Number 1 of 2024 concerning Electronic Information and Transactions (UU ITE). With the increasing development of information and communication technology, social media has become one of the main means of interaction, which at the same time increases the risk of spreading content that is detrimental to a person's good name. This study uses a qualitative method with a comparative approach to analyze changes, advantages, and disadvantages of legal provisions in the latest ITE Law compared to previous regulations. The results of the study show that Law Number 1 of 2024 provides more detailed and firm regulations regarding defamation on social media, with a clearer emphasis on legal boundaries and sanctions. These findings are expected to be a consideration for law enforcers and policy makers in improving legal protection for victims of defamation in the digital era.